First Pass Effect in Patients Treated With the Trevo Stent-Retriever: A TRACK Registry Study Analysis - Mokin, Maxim; Primiani, Christopher T.; Castonguay, Alicia C.; Nogueira, Raul G.; Haussen, Diogo C.; English, Joey D.; Satti, Sudhakar R.; Chen, Jennifer; Farid, Hamed; Borders, Candace; Veznedaroglu, Erol; Binning, Mandy J.; et al. (Frontiers in Neurology, 2020)
Background and Objective: The first pass effect (FPE; achieving complete recanalization with a single thrombectomy device pass) has been shown to be associated with higher rates of good clinical outcomes in patients with acute ischemic stroke. Here, we investigate clinical and radiographic factors associated with FPE in a large U.S. post-marketing registry (TRACK, Trevo Stent-Retriever Acute Stroke). Methods: We analyzed the TRACK database (multicenter registry of 634 patients from 23 centers from March 2013 through August 2015), which 609 patients were included in the final analysis. FPE was defined as a single pass/use of device, TICI 2c/3 recanalization, and no use of rescue therapy. Analysis of individual patient data from TRACK were performed to analyze clinical and radiographic characteristics associated with FPE as well-compared clinical outcomes defined as modified Rankin Scale (mRS) score at 30 and 90 days from hospital discharge to the non-FPE group. Results: The rate of FPE in TRACK was 23% (140/609). There was no association between patient demographics and FPE, including age (p = 0.36), sex (p = 0.50), race (p = 0.50), location of occlusion (p = 0.26), baseline NIHSS (p = 0.62), or past medical history. There was no difference in the use of a balloon-guide catheter or general anesthesia (49 and 57% with FPE vs. 47 and 64%, p = 0.63 and p = 0.14, respectively). Clinical outcomes were significantly associated with FPE; 63 vs. 44% in non-FPE patients achieved mRS 0–2 at 90 days (p = 0.0004). Conclusion: Our study showed that achieving complete recanalization with a single thrombectomy pass using the Trevo device was highly beneficial. The most common clinical factors that are used to determine eligibility for endovascular therapy, such as NIHSS severity, location of occlusion or patient age were not predictive of the ability to achieve FPE.